Violation Analysis on Competitor Sliding Program in the Case of PT Arta Boga Cemerlang (ABC Battery) - Salim, Hartono Agus; Elsa, Elsa; Gymnastiar, Rigan; Silalahi, Udin (International Journal Labs, 2025)
Violations in the Competitor Sliding Program at PT Arta Boga Cemerlang refer to actions that are contrary to business rules and ethics, which aim to unlawfully defeat or harm competitors. The case of PT Arta Boga Cermerlang (ABC Battery) as the Reported Party can be a clear example of violation of the principle of fair business competition, as regulated in Law Number 5 Year 1999. This study employs a legal analysis method to investigate the violations committed by PT Arta Boga Cemerlang (ABC Battery) within the framework of competition law in Indonesia. In this case, PT Arta Boga Cemerlang is proven to have committed unfair business competition practices by entering into a closed agreement that discriminates against products from competitors through exclusive cooperation that provides special benefits to PT Arta Boga Cemerlang's partners. This practice violates Article 15 Paragraph 3 (Closed Agreement) and Article 19 letter (a) (Discrimination) in Law No. 5 Year 1999. Companies that have a dominant position can discriminate in providing services to customers or distributors. Discussing this case in a paper provides an opportunity to analyze how competition law is applied in the context of a market economy, as well as how violations like this can undermine a fair market ecosystem. In addition, the case is also relevant for understanding the challenges of enforcing fair competition principles in a simple and clear manner.